Analisis Implementasi Program Puspa Harapan (Pusat Pangan Sehat Beragam Dan Pasti Aman) Pada Dinas Ketahanan Pangan di Kabupaten Bone - A. Dini Syalsyabila Maharani (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2025)
This study aims to examine and analyze the implementation of the Puspa Harapan Program (Center for Healthy, Diverse, and Safe Food) at the Food Security Agency of Bone Regency. The research was conducted at the Food Security Agency of Bone Regency. The data used in this study consisted of primary and secondary data. Data were collected through observation, interviews, literature review, and documentation. The data were analyzed using a qualitative analytical approach. The results of the study indicate that the implementation of the Puspa Harapan Program (Center for Healthy, Diverse, and Safe Food) in Bone Regency, based on the Strategic Plan of the Food Security Agency (Renstra BKP) 2020–2024, has been implemented relatively well. The program has contributed to improving food security, supporting food diversification, and reducing food vulnerability and stunting rates in the region. However, several aspects still require improvement, particularly in strengthening promotional activities and providing continuous education to the community regarding healthy, diverse, nutritious, balanced, and safe food consumption.